Lived Experiences Of Left-behind Children In Henan Province, China - Lei, Daxia (2024)
Since China’s reform and opening up, there has been a significant migration of surplus labourers from rural to urban areas. As a result, a growing population of children has been left behind in rural settings. These children face educational and psychological challenges that have emerged as important social issues. This study aims to explore the main challenges faced by these left-behind children, examine their coping strategies, and identify their specific needs. Additionally, the study seeks to develop an intervention model to improve their well-being. Conducted in Zhoukou City, Henan Province, the research focused on the care services provided for left-behind children. This study utilizes qualitative research methodology and employs the in-depth interview technique to gather data. Twenty-five (25) left-behind children were interviewed to understand their challenges, coping strategies, and specific needs. The study found disparities in living conditions and familial environments between left-behind children and those who were not left behind, contributing to the health vulnerabilities of left-behind children. Key findings include reduced interaction with parents, difficulties in forming interpersonal relationships, academic performance challenges, and the need for life skills acquisition. Left-behind children employ various coping mechanisms, such as recreational activities, emotional recalibration, seeking support, and taking proactive initiatives. Additionally, the study identified the needs of left-behind children, including the implementation of social work service programs, family care and support, educational engagement, community development and services, as well as national financial and policy support.